Win or Lose the Battle for Creativity: The Power and Perils of Intergroup Competition - Baer, Markus; Leenders, Roger Th. A. J.; Oldham, Greg R.; Vadera, Abhijeet K. (Academy of Management Journal, 2010)
Integrating and refining social interdependence theory and structural adaptation theory, we examined the effects of intergroup competition on the creativity of 70 four-person groups engaged in two idea generation tasks. We manipulated both group membership change (change, no change) and intergroup competition level (low, intermediate, high). Competition had the expected U-shaped relation with creativity in open (membership change) groups but failed to produce the hypothesized inverted U-shaped pattern in closed (no membership change) groups. In the latter, effects were positive for low to intermediate competition and flat for intermediate to high levels. Within-group collaboration mediated these effects.